Investigation of dental health and salivary microbiota characteristics of children with visual impairment in Guangzhou, China - Qiong feng; Wengyan Huang; Xuedan Zhao; Ting Sheng; Bo Peng; Si Meng; Weijia Liu; Lihong Ge; Lijing Wang; Janak Lal Pathak; Qianzhou Jiang; Rong Lin; et al. (BMC Oral Health)
Abstract Background The prevalence of visual impairment (VS) among children in China is increasing. The oral microbiome is crucial for maintaining homeostasis and health. This study aimed to investigate the oral health and hygiene habits of children with VS in Guangzhou and explore the differences in salivary microbiota (SM) between children with VS and healthy vision (HS). Method This study included oral health examinations and surveys of oral hygiene habits among 101 children with VS. Saliva samples from 20 children with VS and 20 with HS were analysed for oral microbiota. The 16s rRNA V3-V4 regions were sequenced using the Illumina MiSeq platform and operational taxonomic units were clustered using QIIME for statistical analysis. Results Inadequate oral hygiene was observed among 101 children with VS, aged 6–16, who displayed a high caries rate of 92.1%. There was no significant difference in the overall composition of the salivary microbiota between the two groups. HS group had a higher abundance of Bacillota, Patescibacteria, and Spirochaetota at the phylum level; Bacilli, Negativicutes, and Saccharimonadia at the class level; and Streptococcus at the genus level. In contrast, VS group showed a greater abundance of Actinomycetota, Bacteroidota, Pseudomonadota, and Fusobacteriota (at the phylum level) and Actinomycetia, Bacteroidia, Gammaproteobacteria, Fusobacteriia, and Clostridia (at the class level), along with Rothia, Neisseria, Veillonella, Prevotella_7, Actinomyces, Leptotrichia, and Lactobacillales (at the genus level). Actinomycetota was significantly and positively correlated with gingivitis and dental caries, and Streptococcus salivarius was more abundant in children with VS. Conclusion This study underscores the importance of improving oral healthcare for schoolchildren with VS in Guangzhou, China and provides valuable insights into the characteristics of the salivary microbiota of this population, identifying potential targets for interventions aimed at enhancing oral health.